INTEGRASI MANAJEMEN KURIKULUM SEBAGAI UPAYA PENINGKATAN MUTU PEMBELAJARAN DI SEKOLAH - Ali Priyono; Ahmad Nur Ismail; Riyas Nur Wardani; Dewi Mardiyanti; Latifatul Bariroh (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2021)
The purpose of this study was to determine the integration of curriculum management in Roushon Fikr Islamic Elementary School Jombang in improving the quality of learning. The locus of this research was taken, because SDI Roushon Fikr is an Islamic educational institution that was present in the era of the industrial revolution 4.0, and is located in the santri city of Jombang as the basis of a large Islamic boarding school in East Java. The research method used is a qualitative descriptive approach, with data mining techniques through observation, interviews, and relevant documentation as secondary data. The results showed that; first, planning the curriculum at SDI Roushon Fikr carefully and structured at the beginning of each year, but still needs to align the process of preparing the lesson plan (RPP), syllabus, and learning tools that are adjusted to the educational calendar and effective week; second, the organization of learning at SDI Roushon Fikr is carried out by representatives of the school in the field of curriculum, through the stage of division of responsibilities for each teacher that is relevant to the field of expertise of each teacher; third, the implementation of the curriculum and the relevance of the quality of learning at SDI Roushon Fikr, starting with opening activities, core activities, and closing activities; fourth, the monitoring and evaluation of the curriculum is carried out by the principal through supervising the school representatives in the curriculum field and the subject teachers in every semester and every year.